SUMBER SENI INDONESIA LAMA - Akhmad Nizam (Institut Seni Indonesia Yogyakarta, 2012)
Modern Art of Indonesian is rich of mozaik. The result from combination of estheticekspression of traditional and non traditional. Some element can be arrange in modern art is theevolution from prehistoric art that buried from the prest. The relation from traditional art andmodern art become symbiosis. Exactly modern art has been appropriate with some genre in art,infact in comtamprorary art. There any attraction with Etnic art as reminder about the presistant asancient tradition.In papper/article has been explorated about the ekspression of tradition art wich already givea beg influence, create, and also develop any responsibility about the evolution of art in Indonesianformany years. The traditional culture have much the glories of bronze age in southeast Asia. At thebegining a sign and symbol have been stated on a cave as art, a megalith statue, and any kind oftradition motive/theme for worship of anchestral spirits. Their cultural hesitge are delicate carvingsengraved on brame ritual tools, magic carvings on war shields and elaborate ceremonial symbol fromthe bronze artifact.Keyword : Last Art, Artifact.